Numerical study of the centre region acceleration for the RIC-30 cyclotron - Andreeva, Z.A.; Svistunov, Yu.A.; Silaev, S.A.; Stepanov, A.V. (Вопросы атомной науки и техники, 2004)
The RIC-30 cyclotron was designed for acceleration of protons up to 30 MeV [1]. Since 1994 it has been used
for production of radionuclides on internal target installed at a radius of 580 mm, where the beam energy equals
22 MeV. Final radius of acceleration is 655 mm. At present, in the long-time irradiation mode the beam current on
target is 190...200 µA [2]. The main objective of the work is to attain a higher beam current due to optimizing configuring of components forming the central ion-optical system of the cyclotron. RIC-30 циклотрон був розроблений для прискорення протонів до 30 МеВ. З 1994 p. він використовувався
для виробництва радіонуклідів на внутрішній мішені, встановленої на радіусі 580 мм, де енергія пучка
дорівнювала 22 МеВ. Кінцевий радіус прискорення дорівнює 655 мм. В даний час при тривалому режимі
опромінення струм пучка на мішені – 190...200 мкА. Основною метою роботи є одержання більш високого
струму пучка внаслідок оптимізації конфігурації компонент, що формують центральну іон-оптичну систему
циклотрона. RIC-30 циклотрон был разработан для ускорения протонов до 30 МэВ. С 1994 г. он использовался для
производства радионуклидов на внутренней мишени, установленной на радиусе 580 мм, где энергия пучка
равнялась 22 МэВ. Конечный радиус ускорения равен 655 мм. В настоящее время при длительном режиме
облучения ток пучка на мишени – 190...200 мкА. Основной целью работы является получение более высокого тока пучка вследствие оптимизации конфигурации компонент, формирующих центральную ион-оптическую систему циклотрона.